PENGARUH FINANCIAL TECHNOLOGY TERHADAP KINERJA KEUANGAN PERBANKAN KONVENSIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2017-2021 - Indrianti, Salma; Gamayuni, Rindu Rika; Susilowati, Retno Yuni Nur (Universitas Multimedia Nusantara, 2022)
Abstract” The application of financial technology (fintech) in the banking industry aims to enable banks to support innovation in the provision of digital services to encourage financial inclusion and public access to financial services. Banking fintech services in this study were measured using mobile banking, internet banking, and SMS banking. Meanwhile, banking financial performance is measured using return on assets (ROA), return on equity (ROE), and net interest margin (NIM). In this study used the control variable, namely the capital adequacy ratio (CAR). However, there are several issues related to the use of fintech services, firstly the increase in users of this service tends to increase bank operational costs (promotion, education, and technology investment), secondly related to security, and thirdly, there is a change in the financial ecosystem due to digitalization. This study uses a sample of all conventional banks that have implemented fintech services and are listed on the Indonesia Stock Exchange (IDX) in 2017-2021. The sample method used is purposive sampling with the analytical method, namely multiple linear regression. Based on the existing sample method, a sample of 20 banks was obtained so that a total sample of 100 observations over a five-year period. The results of multiple linear regression analysis on ROA show that only mobile banking has a positive effect, while internet banking, SMS banking, and CAR do not have a positive effect on the ROA variable. The results of multiple linear regression analysis on ROE show that mobile banking, internet banking, SMS banking, and CAR have no positive effect on the ROE variable. And the results of multiple linear regression analysis on NIM show that mobile banking, SMS banking, and CAR has a positive effect, while internet banking has no positive effect on the NIM variable. Keywords: Financial Technology (fintech); Mobile Banking; Internet Banking; SMS Banking; Return on Asset (ROA); Return on Equity (ROE); Net Interest Margin (NIM); Kinerja Keuangan